2008
DOI: 10.1007/s00595-007-3719-x
|View full text |Cite
|
Sign up to set email alerts
|

The course of pregnancy and delivery in a patient after a double-outlet right ventricle Fontan repair and the influence of this procedure on her general condition: Report of a case

Abstract: The course of pregnancy and delivery in a patient after Fontan repair of double-outlet right ventricle is herein presented. She uneventfully delivered a healthy infant in good general condition at 38 weeks of gestation through a caesarean section, at 24 years after cardiosurgery. Although the patient demonstrated a good hemodynamic state after the operation and conceived while being clinically stable, a worsening of her general condition was observed. After a 4-year follow-up it was clear that pregnancy and de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 8 publications
0
13
0
Order By: Relevance
“…The rate of fi rst-trimester spontaneous miscarriages in the Fontan population is approximately 33%, which is double the rate in healthy females. [1][2][3][4] In the present case, the TCPC conversion was performed after childbirth. However, the patient's pregnancy and delivery triggered a breakdown in the AP Fontan circulation, as indicated by chronic AT and obvious deterioration in the NYHA functional class after pregnancy.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The rate of fi rst-trimester spontaneous miscarriages in the Fontan population is approximately 33%, which is double the rate in healthy females. [1][2][3][4] In the present case, the TCPC conversion was performed after childbirth. However, the patient's pregnancy and delivery triggered a breakdown in the AP Fontan circulation, as indicated by chronic AT and obvious deterioration in the NYHA functional class after pregnancy.…”
Section: Discussionmentioning
confidence: 90%
“…Indeed, there have been only a few reports of successful pregnancies and deliveries in those who have undergone such a procedure. [1][2][3][4] In addition, Fontan conversion is sometimes necessary in adults who begin to show symptoms of failing Fontan circulation. 5, 6 We herein describe a patient who underwent a Fontan conversion 2 years after she successfully delivered a healthy female infant.…”
Section: Introductionmentioning
confidence: 98%
“…These results encouraged us to further review the outcome for pregnancy in UVH patient without surgical correction in the literature, as summarized in Table 2. Surprisingly, all of the reported cases since 1963 show good outcomes [1,2,4,[10][11][12][13][14][15][16][17][18][19][20][21][22]. It was suggested that UVH is not an absolute contraindication to pregnancy.…”
Section: Discussionmentioning
confidence: 95%
“…To our best knowledge, a total of 9 cases of pregnancy in UVH patients have been reported since 2000 [1,2,[9][10][11][12][13], the results are summarized in Table 1. Except for one case [12] that showed severe maternal symptoms and obvious fetal growth delay with oligohydramnios and received a termination of pregnancy at 27-week gestation, all of the other 8 cases had a good outcome for both mother and fetus. These results encouraged us to further review the outcome for pregnancy in UVH patient without surgical correction in the literature, as summarized in Table 2.…”
Section: Discussionmentioning
confidence: 95%
“…71,77 The process of pregnancy and delivery may also have a harmful effect on long-term cardiovascular function in women who have undergone a Fontan repair. 78 Although pregnancy is tolerated in asymptomatic patients with good ventricular function, no pulmonary hypertension, and oxygen saturation greater than 85%, there is still up to a 2% risk of maternal death. 9 Until further data become available, caution is advised regarding childbearing in women post-Fontan repair.…”
Section: Post-fontan Palliationmentioning
confidence: 99%